2000
DOI: 10.1080/003655900750016698
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Registration of all Patients in a Geographical Region with Newly Diagnosed Bladder Carcinomas during a Two-year Period

Abstract: Differences in mean age, stage and grade distribution were found between the present report, which included all patients with newly diagnosed bladder carcinoma in a geographical area, and other reports, which mainly comprised patients from large treatment centres. These differences can probably and mainly be explained by selection factors such as various degrees of inclusion of low-grade papillary tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…to arsenic, but this requires further investigation. It is conceivable, although unlikely, that the similarity of the results to those of Holmäng et al [14,28] from Scandinavia could in part be related to similar ethnic mix, levels of industrialization, lifestyle or other demographic characteristics, rather than to the population-based character of the study population. Future analyses to evaluate potential histological patterns associated with exposure history may provide helpful etiological clues.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…to arsenic, but this requires further investigation. It is conceivable, although unlikely, that the similarity of the results to those of Holmäng et al [14,28] from Scandinavia could in part be related to similar ethnic mix, levels of industrialization, lifestyle or other demographic characteristics, rather than to the population-based character of the study population. Future analyses to evaluate potential histological patterns associated with exposure history may provide helpful etiological clues.…”
Section: Discussionmentioning
confidence: 47%
“…The present findings suggest that the distribution of tumor types may vary by gender and age, and thus the demographics of the selected referral population could affect the distribution of tumor types. Table III compares pathological stage distribution between the present population-based study and representative previously reported studies [8][9][10][11][12][13][14]21,22], all but one of which [14] were based on selected, hospital-or clinic-based patient populations. The hospital-or clinic-based series show a range of non-invasive (stage pTa) tumors between 30 and 49%, compared with 66% in this population-based sample.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations